The Exclusion Process in Education in Indonesia: an Analysis of Social and Policy Deprivation Factors - Dede Sunarya (International Journal Labs, 2025)
This study discusses social exclusion in the context of education in Indonesia, emphasizing that the gap in access to education is not only caused by economic factors alone, but also by structural factors such as non-partisan policies, access inequality, unequal regional development, and discrimination based on gender, ethnicity, and culture. Using a qualitative approach based on an extensive literature study, this study maps the relationship between social exclusion and deprivation both relative and absolute that hinder access to education for vulnerable groups. The results of the study show that although the government has launched various affirmative programs such as scholarships, operational assistance, and the Independent Learning-Independent Campus (MBKM) program, their implementation often creates new forms of exclusion. These programs are considered to have not fully touched the structural and cultural roots of the causes of educational exclusion. Therefore, this study recommends the need for an inclusive, critical, and participatory policy approach, as well as the improvement of the evaluation and transparency system of education programs so that they are not only symbolic but able to create equal access to education for all levels of society.